SLE inflammatory musculoskeletal abnormalities, confirmed by MRI, show a specific profile with a worse health-related quality of life - Corzo, Patricia; Agustí Claramunt, Anna; Garcia-Duitama, Ivan; Carrión-Barberá, Irene; Marsico, Salvatore; Duran Jordà, Xavier; Monfort Faure, Jordi; Salman-Monte, Tarek-Carlos (Lupus, 2025)
Objectives To determine if there is a clinicodemographic or serological profile associated with MRI-confirmed inflammatory musculoskeletal abnormalities in SLE patients. To investigate the relationship between these alterations and HRQoL. Methods patients with SLE from our previous study in whom a wrist and hand MRI with contrast was performed were included. Sociodemographic, clinical, therapeutic, serological data and PROs were collected and correlated with MRI findings. Results 83 patients were analysed. Erosions and synovitis were more common in older patients (55 ± 12.61 vs 45.06 ± 12.18 years, p .001, 52.78 ± 12.99 vs 44.95 ± 12.49 years, p .011). Synovitis was less frequent in patients with nephritis (6.7% vs 24.3%, p .031). Treatment received showed some associations: patients with bone edema received more methotrexate (25% vs 6.3%, p .033), those with erosions and peritendonitis received less mycophenolic acid (5.6% vs 22.9%, p .034; 0% vs 12.8%, p .026). Peritendonitis correlated with higher SLEDAI-2K (7 ± 2.45 vs 3.64 ± 3.34, p .018). Worse HAQ Patients with synovitis, tenosynovitis, peritendonitis and bone edema reported higher pain (6.03 ± 2.57 vs 4.26 ± 2.49, p .005; 6.56 ± 1.95 vs 4.76 ± 2.75, p .017; 8.80 ± 1.30 vs 4.95 ± 2.55, p .001; 6.47 ± 2.62 vs 4.83 ± 2.58, p .026, respectively). Patients with synovitis reported higher fatigue numerical values (2.32 ± 0.82 vs 1.91 ± 0.84, p .035), with tenosynovitis worse FSS-9 (61.50 ± 1.73 vs 45.70 ± 16.80, p .015), and with both synovitis and peritendonitis worse HAQ (1.14 ± 0.69 vs 0.75 ± 0.65, p .031; 1.69 ± 0.07 vs 0.90 ± 0.69, p .018). Conclusion SLE patients with confirmed musculoskeletal alterations on MRI were generally older, less likely to have lupus nephritis, and received different treatments. They reported a worse HRQoL in terms of pain, fatigue and functional disability.